Hidrovia do Amazonas: riscos à navegação no trecho de Santana (Amapá) à Belém (Pará), no período de 1986 a 2006 - CRIZANTO, Aline Cavalcante (2019)
Brazil has more than 40,000 km of viable inland navigation waterways, one that is exclusively practiced in rivers, involving vessels carrying a variety of loads. However, it is obvious that this potential has been underutilized, because it is also an area that suffers of lack of studies that contribute to its sustainable use. Among the relevant aspects concerning the use of waterways, there is the safety of navigation. A waterway can be considered viable if it is endowed with structures that ensure safe conditions to who use it, what makes this theme a relevant aspect to be studied. The improvement in the use of a waterway means a breakthrough in the development of the region in which it finds itself. Remarkably, within a regional context, the need for studies on the stretch of the waterway of the Amazon, that connects the cities of Belém-PA and Santana-AP. Thus, this work was developed under the perspective of changing the importance of this waterway, and as a tool for multitemporal understanding between the years of 1986 and 2006. The data obtained in industry surveys of the Port of Eastern Amazonia (CPAOR), and using Geographic Information System (GIS) were used for the spatial distribution of incidents recorded, beyond the boundaries of the existing shoreline at different times (1986, 2006), required for visual interpretation of existing physiographic changes, which may serve for future verification of the relationship of these changes with the occurrence of accidents.